FAPI Tracer en Vogue: Evaluating [68Ga]Ga-DATA5m.SA.FAPi for Molecular Imaging of Pulmonary Fibrosis - Weissenböck, Victoria; Schlederer, Michaela; Bakiri, Latifa; Schaffenrath, Johanna; Wagner, Erwin F.; Rösch, Frank; Hacker, Marcus; Kenner, Lukas; Philippe, Cécile (Pharmaceuticals (Basel, Switzerland))
Background/Objectives: Radiolabeled fibroblast activation protein inhibitors (FAPIs) are emerging as promising imaging agents assessing fibrotic diseases. This study evaluates [68Ga]Ga-DATA5m.SA.FAPi for imaging pulmonary fibrosis in two mouse models, bleomycin-induced (BLM) and a transgenic (fra-2tg) model, both displaying characteristics of human pulmonary fibrotic diseases. Methods: In the BLM model, C57BL/6 mice were treated with bleomycin or isotonic sodium chloride (controls) for 4, 5, and 6 weeks, followed by [68Ga]Ga-DATA5m.SA.FAPi PET/CT scans. Fra-2tg mice and wildtype (WT) littermates underwent at 7, 11, and 18/19 weeks of age a PET/CT scan. The selected timepoints correspond to early, middle, and late disease stages for each model. Imaging was complemented by ex vivo quantification, histological, and immunohistochemical (IHC) analyses. Results: In BLM mice, pulmonary [68Ga]Ga-DATA5m.SA.FAPi uptake showed a trend toward increase as early as 5 weeks of treatment compared with the controls, which was confirmed by ex vivo analysis (BLM: 3.31 ± 0.29%ID/g, n = 5; control: 1.61 ± 0.29%ID/g, n = 4; p = 0.0035). In fra-2tg mice, no significant differences could be detected. IHC revealed elevated pulmonary FAP expression specifically at early (BLM) and mild (fra-2tg) disease stages, whereas for BLM, tracer uptake was more pronounced at later stages. Conclusions: Our findings complement and extend observations from previous studies and support the potential of FAPI tracers as molecular imaging agents for pulmonary fibrosis.